The relationship of the level of metacognitive thinking and decision-making to execution of offensive technical tactical actions in soccer - Bellem, Issam (Journal of Human Sciences, 2021)
This study aimed to identify the nature of the relationship between the level of metacognitive thinking and decision-making for the execution of offensive technical-tactical actions in students of the national high school of sports specializing in football. The sample consisted of (21) students from the National School of Secondary Sports - Sahal Ibrahim supplement in the wilaya of Oum El Bouaghi. Two tools were applied to the sample, the first is the scale of metacognitive thinking, of El-Jarrah and Obaidat (2011), and the second is the Tool (GPET) which measures decision making and execution of offensive tactical skills in football prepared by García Lopez et al. in 2013. The results showed the following: - There is a correlative relationship with the level of metacognitive thinking and decision-making for the execution of offensive technical-tactical actions of sports high school students, specialized in football.